Sepsis survivors monitoring and coordination in outpatient health care (SMOOTH): study protocol for a randomized controlled trial - Schmidt, Konrad; Thiel, Paul; Mueller, Friederike; Schmuecker, Katja; Worrack, Susanne; Mehlhorn, Juliane; Engel, Christoph; Brenk-Franz, Katja; Kausche, Stephan; Jakobi, Ursula; Bindara-Klippel, Anne; Schneider, Nico; et al. (Trials, 2014)
BACKGROUND Sepsis sequelae include critical illness polyneuropathy, myopathy, wasting, neurocognitive deficits, post-traumatic stress disorder, depression and chronic pain. Little is known howlong-term sequelae following hospital discharge are treated. The aim of our study is to determine the effect of a primary care-based, long-term program on health-related quality of life in sepsis survivors. METHODS/DESIGN In a two-armed randomized multicenter interventional study, patients after sepsis (n = 290) will be assessed at 6, 12 and 24 months. Patients are eligible if severe sepsis or septic shock (ICD-10), at least two criteria of systemic inflammatory response syndrome (SIRS), at least one organ dysfunction and sufficient cognitive capacity are present. The intervention comprises 1) discharge management, 2) training of general practitioners and patients in evidence-based care for sepsis sequelae and 3) telephone monitoring of patients. At six months, we expect an improved primary outcome (health-related quality of life/SF-36) and improved secondary outcomes such as costs, mortality, clinical-, psycho-social- and process-of-care measures in the intervention group compared to the control group. DISCUSSION This study evaluates a primary care-based, long-term program for patients after severe sepsis. Study results may add evidence for improved sepsis care management. General practitioners may contribute efficiently to sepsis aftercare. TRIAL REGISTRATION U1111-1119-6345. DRKS00000741, CCT-NAPN-20875 (25 February 2011).